The Effect of the Dose of the Proportion of Organic Fertilizer with NPK on the Management of Cashew Stands on the Growth and Yield of Plants, as Well as its Capacity for the Maintenance of Cattle - I Ketut Ngawit; I Wayan Sudika; Wayan Wangiyana (Postgraduate, University of Mataram, 2025)
The reason for the low productivity of cashew in the Indonesian province of West Nusa Tenggara is that they are never cared for and the land between the cashew tree rows is not intensively cultivated. The first factor is the type of organic fertilizer: cow, horse, and chicken manure; a mixture of cow + horse manure, cow + chicken manure, and horse + chicken manure. The second factor is the dosage ratio of organic fertilizer: 35 tons + NPK 0 kg ha-1, 25 tons + NPK 250 kg ha-1, 15 tons + NPK 500 kg ha-1, and 0 tons + NPK 750 kg ha-1. The application of organic fertilizer from a mixture of cow and chicken manure at a dose of 15-25 tons + NPK 250-500 kg ha-1 significantly increases soil fertility status and reduces the rate of soil erosion. When applying the best type of organic fertilizer, the dosage ratio of 35 tons + NPK 0 kg ha-1 and 0 tons + NPK 750 kg ha-1, the effect is not significantly different for all parameters. Applying a dose of 15 to 25 tons per hectare can replace the role of NPK fertilizer by 33.33 to 66.67% of the 750 kg per hectare dose and significantly increase the cattle breeding capacity of cashew plantations by up to 5,875 livestock unit hectare-1 season-1